Effect of COVID-19 pandemic on health seeking behavior of children with cerebral palsy and their caregivers - Sattiraju Sarvani; Anju Aggarwal; Narender Kumar (International Journal of Contemporary Pediatrics, 2026)
Background: COVID-19 pandemic exacerbated the already existing challenges face by children with cerebral palsy (CP) and their caregivers. This study was conducted to analyze the effect of COVID-19 pandemic on the health seeking behavior of children with CP and their caregivers. Methods: Parents/ caregivers of sixty-one children, who could be contacted were asked a set of questions using a pre-structured questionnaire including demographic details, information related to change in health status and reasons for change in health seeking behavior during and after pandemic. Results: Out of 61 caregivers, 34 (55.7%) reported worsening in child’s health after COVID-19. 59 (96.7%) caregivers reported decrease in the frequency follow up visits after COVID-19 pandemic. The 38 (62.3%) shifted to rehabilitation at home by self. 59 (96.7%) caregivers reported consultation at hospital and two (3.3%) cases at private clinics during acute illness before COVID-19 pandemic. Fear of COVID infection was cited as most common reason for change followed by closure of health facilities during COVID pandemic. Post covid, irritability increased in 23% cases, tone increased in 54.1% cases, contractures increased in 6.6% cases, seizures increased in 27.9% cases. Conclusions: Children with CP and their caregivers need special care during major events such as pandemic to avoid negative impact on their health status.